On Naturalism in Hegel's Philosophy of Spirit*. Issue 1 (2nd January 2016) - Peters, Julia
Abstract : In recent years, philosophers have become increasingly interested in a Hegelian approach to Aristotelian non-reductive naturalism. This paper points out a challenge faced by naturalist readings of Hegel's conception of spirit. For Hegel, spirit and nature are essentially distinct and even related in an antagonistic way. It is difficult to do full justice to this thought while at the same time reading Hegel as a naturalist. The paper also seeks to suggest a response to this challenge. Drawing on Hegel's account of mechanism in his philosophy of spirit, it shows that processes which can count as natural – such as mechanical processes – constitute for Hegel an integral and indispensable part of spiritual activity. Against this background, it is possible to develop a form of Hegelian naturalism which does not lose sight of the essential distinction, even opposition of spirit and nature.